2014
DOI: 10.5152/tftrd.2014.34033
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Osteoporosis in the Thrace Region of Turkey: A Community-Based Study

Abstract: Objective: This study was planned as a community-based research study to estimate the prevalence of osteoporosis and explore related risk factors in the Thrace region of Turkey. Material and Methods:The community-based study involved a total of 620 people, 498 women and 122 men, aged between 40 and 89 years. A questionnaire on the medical history and lifestyles of the participants was applied with a face-to-face interview. Body weight height, and arm span of each participant were measured, together with bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
10
0
1
Order By: Relevance
“…Two of the studies claimed tea consumption to have a beneficial impact on BMD compared with non-tea consumption [28,29] ; no correlation between them was found in the remaining 3 studies. [26,27,30] The pooled results showed that tea consumption could reduce the occurrence of low bone mass (OR = 0.66, 95% CI = 0.47–0.94, P  = 0.02) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the studies claimed tea consumption to have a beneficial impact on BMD compared with non-tea consumption [28,29] ; no correlation between them was found in the remaining 3 studies. [26,27,30] The pooled results showed that tea consumption could reduce the occurrence of low bone mass (OR = 0.66, 95% CI = 0.47–0.94, P  = 0.02) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpected, this study indicated a high prevalence of osteopenia and OP in those patients who were ≤ 50 years and the effect on bone continued for >2 years from the last cycle of chemotherapy [82]. However, others found that hormonal replacement therapy (HRT) and oral contraceptive pills (OCP) have a protective effect on BMD, and those women were less likely to have OP [10].…”
Section: Medicationsmentioning
confidence: 89%
“…In a community-based study involving 620 Turkish people, the prevalence of OP was 15.1% among women and 10.7% among men [10]. High frequencies of OP and osteopenia (58% and 32%, respectively) had been detected among patients admitted to the geriatric department [11].…”
Section: Epidemiology Of Osteoporosis In Menamentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the region of Thrace, OP was revealed to be a significant health problem as 1 in 4 individuals over the age of 55 years were osteoporotic. The prevalence in females was determined as 15.1% and in males over the age of 40 years, 10.7% [9]. Ipek et al [10] determined the OP rate with DEXA as 31.8% in the L1-L4 vertebrae region, as 40.2% in the femoral neck and as 34.3% in at least one area of the L1-L4 vertebrae and/or the femoral neck.…”
Section: Discussionmentioning
confidence: 99%